Natural flavonoids inhibit the plasma membrane Ca 2+ -ATPase - Ontiveros, Mallku Qhapaj (2019)
Research on flavonoids from plant sources has recently sparked increasing interest because of their beneficial health properties. Different studies have shown that flavonoids change the intracellular Ca 2+ homeostasis linked to alterations in the function of mitochondria, Ca 2+ channels and Ca 2+ pumps. These findings hint at plasma membrane Ca 2+ -ATPase (PMCA) involvement, as it transports Ca 2+ actively to the extracellular medium coupled to ATP hydrolysis, thus maintaining ion cellular homeostasis. The present study aims to investigate the effect of several natural flavonoids on PMCA both in isolated protein systems and in living cells, and to establish the relationship between flavonoid structure and inhibitory activity on PMCA. Our results show that natural flavonoids inhibited purified and membranous PMCA with different effectiveness: quercetin and gossypin were the most potent and their inhibition mechanisms seem to be different, as quercetin does not prevent ATP binding whereas gossypin does. Moreover, PMCA activity was inhibited in human embryonic kidney cells which transiently overexpress PMCA, suggesting that the effects observed on isolated systems could occur in a complex structure like a living cell. In conclusion, this work reveals a novel molecular mechanism through which flavonoids inhibit PMCA, which leads to Ca 2+ homeostasis and signaling alterations in the cell.